A prospective cohort study of clinical presentation and outcomes of acute pancreatitis at tertiary care center - Pahuja, Vivek; Rani, Nisha; Singla, Girish; Dugg, Pankaj; Singh, Sarabjit (International Surgery Journal, 2025)
Background: Acute pancreatitis present with varied symptoms and etiologies and had variety of outcomes based on severity. The study was conducted to see the clinical presentation and outcomes of acute pancreatitis at tertiary care center. Methods: The study was carried out on 47 patients of acute pancreatitis. The clinical presentations and outcomes were noted. The severity is assessed by modified computed tomography severity index (MCTSI). Statistical analysis was done on Microsoft Excel version 21. P value<0.05 is considered significant. Results: The mean age of patients was 36.94±10.63 years with male to female ratio of 2.6:1. Alcohol was the common etiological factor seen in 59.57% (n=28). MCTSI score was significant in detecting necrosis (p=0.00001) and predicting mortality (p value=0.000048). Conclusions: Severe acute pancreatitis has high mortality. MCTSI is good prognostic factor for assessing morbidity and mortality.